2010
DOI: 10.2175/193864710798182691
|View full text |Cite
|
Sign up to set email alerts
|

Developing Waterways Asset Management Program that Incorporates Differences between Highly Urban and Semi-Urban or Rural Watersheds in Risks and Management Strategies

Abstract: The principles of Asset Management, have traditionally been applied to Water, wastewater, and transportation Utilities and focused on constructed physical assets. Yet, these principles are applicable to all management functions within a utility or organization. In our case, the principles of asset management have been applied to waterways where the nature of the assets themselves are not all constructed physical structures. The waterways asset management plan we have developed captures conditions along linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Many variations of IAM definitions and objectives exist, resulting in the fragmentation of the concept [24]. Definitions of IAM of roads are focusing mainly on costeffectiveness, while the objectives for rail and inland navigation infrastructure are respectively safety and reliability and service and availability [20,21,[25][26][27][28]. As a consequence of this variety, the management of infrastructure can be compared with the iron triangle in project management, consisting of time, performance and cost.…”
Section: Infrastructure Assets Of a Region And Their Managementmentioning
confidence: 99%
“…Many variations of IAM definitions and objectives exist, resulting in the fragmentation of the concept [24]. Definitions of IAM of roads are focusing mainly on costeffectiveness, while the objectives for rail and inland navigation infrastructure are respectively safety and reliability and service and availability [20,21,[25][26][27][28]. As a consequence of this variety, the management of infrastructure can be compared with the iron triangle in project management, consisting of time, performance and cost.…”
Section: Infrastructure Assets Of a Region And Their Managementmentioning
confidence: 99%
“…Typical Asset Hierarchical Structure for a wastewater or water treatment plant (additional class sub class structure of each asset is not shown)(Sen et al, 2012) Enterprise Name of Utility, not shown in the plant but shown in the database Plant Name of Plant -can be water plant, wastewater plant…”
mentioning
confidence: 99%